1977
DOI: 10.1302/0301-620x.59b4.925057
|View full text |Cite
|
Sign up to set email alerts
|

The muscles in club foot--a histological histochemical and electron microscopic study

Abstract: In talipes equino-varus the diminished bulk of the calf muscle suggests a neuromuscular defect. Accordingly, biopsies were taken from the postero-medial and peroneal muscle groups, and occasionally from abductor hallucis, in sixty patients mostly under the age of five years; 111 were studied histochemically and histologically, and a further fifty-three by electron-microscopy. Histochemical anomalies were revealed in ninety-two specimens; the muscle fibres in the other nineteen varied in size but were abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
11

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 23 publications
1
38
0
11
Order By: Relevance
“…Recent biopsy studies of the extrinsic muscles of the calf during clubfoot surgery have demonstrated fiber type disproportion, reduction in the number of muscle fibers, increased neuromuscular junctions, and electron microscopic abnormalities [22,24,33]. The normal ratio of type I to type II fibers is 1:2 but in clubfeet the relationship is approximately 7:1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent biopsy studies of the extrinsic muscles of the calf during clubfoot surgery have demonstrated fiber type disproportion, reduction in the number of muscle fibers, increased neuromuscular junctions, and electron microscopic abnormalities [22,24,33]. The normal ratio of type I to type II fibers is 1:2 but in clubfeet the relationship is approximately 7:1.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the frequency of talipes equinovarus in neurological disorders, no consistent neuromuscular abnormalities have been identified in isolated talipes equinovarus patients using muscle biopsy or electrophysiological examinations. [4][5][6][7] Most cases of clubfeet (80%) occur as isolated birth defects and are considered idiopathic. 8 Approximately 25% of patients with isolated talipes equinovarus report a family history of talipes equinovarus, suggesting a genetic basis for this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…With etiology still unknown, several theories were proposed to explain the origin of CC, considering intrinsic or extrinsic causes, including: intrauterine position of the fetus, mechanical compression or increase of intrauterine hydraulic pressure 10,11 ; interruption in fetal development 12 ; viral infections 13 ; vascular deficiencies 14,15 ; muscular alterations [16][17][18][19][20] ; neurological alterations [21][22][23][24][25][26][27] ; defect in the development of bones structures 3,28,29 and genetic defects. 7,[30][31][32][33][34][35][36][37][38][39] The discovery of the existence of fibrotic tissue in the muscles, fasciae, ligaments and tendon sheaths of the posteromedial region of the ankle and hindfoot 18,20 corroborates the hypothesis of primary defect of soft parts and neuromuscular units that lead to bone alterations.…”
Section: Etiologymentioning
confidence: 99%
“…7,[30][31][32][33][34][35][36][37][38][39] The discovery of the existence of fibrotic tissue in the muscles, fasciae, ligaments and tendon sheaths of the posteromedial region of the ankle and hindfoot 18,20 corroborates the hypothesis of primary defect of soft parts and neuromuscular units that lead to bone alterations. 16,18,21,22,24,26,40 The cytocontractile proteins and myofibroblasts identified in the posteromedial contractured tissues of the hindfoot 30,34 are structurally similar to those present in palmar fibromatosis and express high levels of type III collagen and certain growth fac-tors, when compared to the non-contractured tissues. 41,42 Shortening, fibrosis and retraction of the muscles and ligaments in CC are said to be genetically induced, resulting in abnormal retraction capacity that could possibly be related to primary congenital deformities and also to relapses that occur, even after adequate treatment.…”
Section: Etiologymentioning
confidence: 99%